Epidemiology, molecular strain types, and macrolide resistance of Treponema pallidum in Japan, 2017–2018. Issue 10 (October 2020) - Nishiki, Shingo; Arima, Yuzo; Kanai, Mizue; Shimuta, Ken; Nakayama, Shu-ichi; Ohnishi, Makoto
Abstract: Background: Japan has seen a substantial increase in syphilis cases since 2013 and Tokyo and Osaka prefectures accounted for about 40% of all cases in Japan. Therefore, focusing on these 2 prefectures, we assessed syphilis cases detected during 2017–2018, combining epidemiological information with molecular typing data. Methods: Using data from surveillance reports, we described syphilis cases by gender, age, transmission route, and stage of syphilis. Clinical specimens were collected from syphilis patients in Tokyo and Osaka prefectures. Molecular typing was performed by analyzing Treponema pallidum arp, tpr, and tp0548 genes, with partial sequencing of the 23S rRNA genes for macrolide resistance. Results: Between 2017 and 2018, the number of syphilis cases increased from 3934 to 4588 among males and 1895 to 2414 among females, with similar age and gender distributions during the period. The predominant strain type was 14d/f (71%, 73/103), found more frequently in women who have sex with men (86%, 25/29) and men who have sex with women (83%, 39/47) than in men who have sex with men (MSM) (33%, 9/27). The majority of the strains from heterosexuals (97%, 76/78) were macrolide-resistant, considerably higher than those from MSM (59%, 20/34). The molecular profiles in each sexual-transmission group remained similar during the 2 years. Conclusions: The epidemiological and molecular features of syphilis remained similar throughout the period, with consistent differences in strain type and macrolide resistance distributions between MSM and heterosexual cases. These findings suggest a predominantly heterosexual epidemic where the dynamics of syphilis transmission remained unchanged during 2017–2018.